2007
DOI: 10.1002/pon.1146
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term psychosocial adjustment of older vs younger survivors of breast and endometrial cancer

Abstract: Survivors reported few cancer-related problems with only a small subset reporting problems in adjustment. Although differences were small, younger cancer survivors reported significantly worse adaptation than older survivors. Much of the adaptation to having had cancer may have already occurred in long-term survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
2
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 36 publications
14
140
2
13
Order By: Relevance
“…With growing age, physical problems are likely to increase, even irrespective of the cancer diagnosis. However, the finding that age was not predictive of other QoL domains contradicts the hypothesis, as well as previous studies that have reported greater distress in younger breast cancer patients in both the short term and long term [7][8][9]. This greater impairment of QoL in the younger age group was explained by greater work-related and family-related demands, less adequate strategies for coping with disease, and health-related restrictions.…”
Section: Age As a Sociodemographic Predictor And Oncological Predictorscontrasting
confidence: 55%
See 2 more Smart Citations
“…With growing age, physical problems are likely to increase, even irrespective of the cancer diagnosis. However, the finding that age was not predictive of other QoL domains contradicts the hypothesis, as well as previous studies that have reported greater distress in younger breast cancer patients in both the short term and long term [7][8][9]. This greater impairment of QoL in the younger age group was explained by greater work-related and family-related demands, less adequate strategies for coping with disease, and health-related restrictions.…”
Section: Age As a Sociodemographic Predictor And Oncological Predictorscontrasting
confidence: 55%
“…The selection of age, tumor size, axillary surgery, and adjuvant chemotherapy as sociodemographic and oncological impact factors on the QoL of breast cancer patients is based on clinical studies [1][2][3][4][5][6][7][8][9]. The impact of primary surgical treatment (BCT vs mastectomy), especially in relation to long-term body image, would also have been of interest [3,5], but the very small subgroup of patients treated with mastectomy (8%) did not allow statistical analysis.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score on this questionnaire indicates better body image. The average scores for the dragon boaters in the current study was 3.03 ± 0.4, (Range = 2.29-3.57), which was significantly higher than the non-dragon boating survivors (2.58 ±0.81; p = 0.018) (Kornblith et al, 2007).…”
Section: Psychosocial Measurements: Dragon Boat Racing Versus Populatmentioning
confidence: 91%
“…Scores were compared with subjects in a study of 252 breast and endometrial cancer survivors who ranged in age from 55 to 65 years old, were recruited from 2003 to 2004, and ranged from 2.9 to 4.5 years posttreatment. This population was 93% white while 78% were married (Kornblith et al, 2007). A higher score on this questionnaire indicates better body image.…”
Section: Psychosocial Measurements: Dragon Boat Racing Versus Populatmentioning
confidence: 99%